Food insecurity and its determinants1. (18th September 2014) - Warr, Peter
<x xml:space="preserve">Abstract</x> Expansion of aggregate food supplies within developing countries themselves is strongly associated with reduced undernourishment. It is not sufficient to rely solely on aggregate economic growth or reductions in poverty incidence to deliver improved food security. But the evidence also shows that higher food prices significantly increase the rate of undernourishment. It is therefore important to stimulate agricultural output without raising domestic food prices. Improvements in agricultural productivity achieve that, but agricultural protection aimed at food self‐sufficiency does not, because the objective of reducing imports is achieved through an increase in domestic food prices. Although this process delivers benefits to those food insecure people who are net sellers of food, in most poor countries their number is exceeded by the food insecure people who are net buyers of food. Increased food prices make the latter group more food insecure. Food self‐sufficiency does not imply food security.